2017
DOI: 10.1111/tra.12524
|View full text |Cite
|
Sign up to set email alerts
|

SNARE proteins in membrane trafficking

Abstract: SNAREs are the core machinery mediating membrane fusion. In this review, we provide an update on the recent progress on SNAREs regulating membrane fusion events, especially the more detailed fusion processes dissected by well-developed biophysical methods and in vitro single molecule analysis approaches. We also briefly summarize the relevant research from Chinese laboratories and highlight the significant contributions on our understanding of SNARE-mediated membrane trafficking from scientists in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
126
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(130 citation statements)
references
References 132 publications
1
126
0
3
Order By: Relevance
“…First, co-localization studies using organelle-associated molecular markers, and the FM4-64 marker demonstrated that NISP is associated with TGN/early endosomal vesicles. Second, we confirmed that NISP interacted with NSP in planta and showed that the complex formation occurred in vesicle-like structures, which resemble the NISP-associated TGN/endosomal vesicles, the typical subcellular localization of syntaxin-6-like proteins from Arabidopsis and humans [49]. Third, we showed that NISP exhibits a pro-viral function, and begomovirus infection required NISP-NSP interaction.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…First, co-localization studies using organelle-associated molecular markers, and the FM4-64 marker demonstrated that NISP is associated with TGN/early endosomal vesicles. Second, we confirmed that NISP interacted with NSP in planta and showed that the complex formation occurred in vesicle-like structures, which resemble the NISP-associated TGN/endosomal vesicles, the typical subcellular localization of syntaxin-6-like proteins from Arabidopsis and humans [49]. Third, we showed that NISP exhibits a pro-viral function, and begomovirus infection required NISP-NSP interaction.…”
Section: Discussionsupporting
confidence: 64%
“…SYP61 has been shown to form functional SNARE complexes involved in the vacuolar-TGN recycling pathway and in exocytotic trafficking to the plasma membrane [43, 50]. The process of membrane fusion is the final step of vesicle transport, which is generally driven by a specific pairing of 1 v-SNAREs with the 3 or 3 cognate t-SNARE molecules into a trans-SNARE complex [49, 51]. The proteins from the SYP61 subclade contain the typical structural configuration of t-SNARES, including the N-terminal syntaxin-6 domain, followed by a C-terminal t-SNARE coiled-coil homology domain and a transmembrane segment at the C-terminus.…”
Section: Discussionmentioning
confidence: 99%
“…ORF3a detects 7 components of the SNARE complex (NAPA, STX4/6/7/12/16 and SNAP23) and uniquely interacts with 12 components of the 33A/39/41). The SNARE complex is involved in membrane trafficking and fusion79 ; the TRAPP complex in tethering vesicle transported from ER to Golgi80 ; and the HOPS and CORVET complexes in vacuolar, late endosomal and lysosomal membranes tethering and fusion81 . These data strongly suggest that ORF3a acts as a major regulator of endosomal and membrane trafficking by interfering with vesicular membrane attachment machineries.…”
mentioning
confidence: 99%
“…In accordance with the known involvement of PLDs in vesicle fusions, we observed an increased abundance of alpha-soluble NSF attachment protein 2 (Alpha-SNAP2) in the pldα1-1 mutant. Alpha-SNAP proteins bind the SNARE complex [44] and are required for the vesicle pre-docking, an initial step of the membrane fusion reaction [45,46]. The precise function of alpha-SNAP2 is unknown so far, but it might require PLDα1.…”
Section: Vesicular Transportmentioning
confidence: 99%